A multidimensional approach to self-criticism: development of the self-criticism scale and investigation of its psychometric properties - EKŞİ, HALİL (My University, 2022)
The aim of this research is to develop a scale to determine the self-criticism levels of adults and to examine their psychometric properties. This study, using quantitative research methods, was conducted with 675 adults (18-61 years old) (xm: 25.95; xsd: 6.91). The collected data were analyzed with SPSS 25 and AMOS 24 statistical programs. As a result of the study, the “Self-Criticism Scale” consisting of 30 items and 3 sub-dimensions was obtained. According to the results of the exploratory factor analysis, the three-factor structure explains 48.93% of the total variance. In the analysis made in line with the reliability studies, the Cronbach alpha internal consistency coefficient of the scale was determined as 910 for the destructive self-criticism sub-dimension, .884 for the constructive self-criticism sub-dimension, and .806 for the insufficient self-criticism sub-dimension. As a result of the independent groups t-test performed to determine the discrimination of the scale items, a significant difference was found between the lower and upper groups for all scale items (p<.000). In addition, it is seen that the values of the goodness of fit obtained as a result of the confirmatory factor analysis are within the appropriate reference ranges (χ2/sd=2.472; RMSEA=0.066; SRMR=0.07; IFI=0.961; CFI=0.955; GFI=0.924). The findings obtained as a result of the study reveal that the Self-Criticism Scale (SCS) can be used as a valid and reliable measurement tool in determining the self-criticism levels of adults.
Keywords: Self-Criticism; Destructive Self-Criticism; Constructive Self-Criticism; Insufficient Self-Criticism; Adult; Scale Development